Annual World Bank Conference on Development Economics--Global 2008 : Private Sector and Development - Lin, Justin Yifu; Pleskovic, Boris (Washington, DC: World Bank, 2013)
The Annual World Bank Conference on Development Economics (ABCDE) is a leading forum for advanced, forward-looking research on important development issues. Each year, the ABCDE brings policy makers and politicians together with researchers from academe, international organizations, and think tanks. The diverse perspectives of the international development community mingle and coalesce through in-depth debates on important themes on the development agenda. The 2008 ABCDE was devoted to the theme 'the private sector and development' and highlighted such issues as financial inclusion, key factors in the business climate, and the provision of public services by non-state actors.